2019
DOI: 10.2166/wh.2019.158
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of gross alpha and beta activity concentration in groundwater of Jordan: groundwater quality, annual effective dose and lifetime risk assessment

Abstract: The current study was conducted to measure the activity concentration of the gross alpha and beta in 87 groundwater samples collected from the productive aquifers that constitute a major source of groundwater to evaluate the annual effective dose and the corresponding health impact on the population and to investigate the quality of groundwater in Jordan. The mean activity concentration of gross alpha and beta in groundwater ranges from 0.26 ± 0.03 to 3.58 ± 0.55 Bq L−1 and from 0.51 ± 0.07 to 3.43 ± 0.46 Bq L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
2
7
3
1
Order By: Relevance
“…Also, this validates the prediction of gross alpha activity concentration in the samples. Similar reports are made by Agbalagba et al (2013) and Alomari et al (2019). Figure 11.…”
Section: Relationship Between Beta and Alpha Activity Concentrationssupporting
confidence: 82%
See 2 more Smart Citations
“…Also, this validates the prediction of gross alpha activity concentration in the samples. Similar reports are made by Agbalagba et al (2013) and Alomari et al (2019). Figure 11.…”
Section: Relationship Between Beta and Alpha Activity Concentrationssupporting
confidence: 82%
“…High positive R 2 between the parameters indicates that pH is responsible for the activity concentrations of gross alpha and beta in the samples. This report showed similar trends of significant relationship between the pH and gross alpha and gross beta activity at pH < 8.3 (Alomari et al, 2019). This shows that pH of the samples are responsible for the activity concentration of the gross alpha and beta.…”
Section: Relationship Between Gross Alpha and Beta Activity Concentrasupporting
confidence: 77%
See 1 more Smart Citation
“…In particular, multiple previous studies observed a strong relationship between the gross alpha and beta activity concentrations [24,27,28]. The gross alpha and beta activity concentrations also reportedly show an insignificant relationship with pH values and EC values of groundwater [26]. The correlation observed between gross alpha and gross beta in China was weak (R = .43) [25].…”
Section: Resultsmentioning
confidence: 92%
“…In Jordan, the geological structure is heterogeneous, the level of gross alpha and beta is different in different areas, especially in Aqaba governorate. The high radionuclide level in groundwater in Jordan is attributed to the sandstone rock, which contains abundant thorium-enriched heavy mineral aggregations [26]. The high radionuclide level in groundwater in Turkey (Nevşehir province) is also attributed to the geological structure.…”
Section: Resultsmentioning
confidence: 99%